Branched-chain amino acid transaminases as promising targets in tumor therapy - Zhang, Weiran; Shen, Jie; Ding, Xuanyin; Liu, Hele; Wang, Xu; Feng, Dan (Frontiers in Cell and Developmental Biology, 2026)
Branched-chain amino acid transaminases (BCATs), including BCAT1 and BCAT2, play pivotal roles in tumorigenesis and therapeutic resistance in various cancers. These enzymes regulate branched-chain amino acid (BCAA) metabolism and influence critical oncogenic pathways such as mTOR, PI3K/AKT, and Wnt/β-catenin signalling. Furthermore, BCATs contribute to metabolic reprogramming, epigenetic modifications, and immune evasion. Collectively, they promote tumor proliferation, invasion, and metastasis, thus making BCATs potential biomarkers and therapeutic targets. Recent studies highlight their aberrant expression in cancers including gastric cancer, pancreatic cancer, non-small cell lung cancer, leukaemia, gliomas, and breast cancer, where they contribute to resistance to chemotherapy, targeted therapy, and endocrine therapy. Strategies targeting BCATs, including enzyme inhibitors, dietary BCAA restriction, and combination therapies, have shown the potential to overcome drug resistance and improve treatment outcomes. This review synthesizes current knowledge on the mechanisms of BCATs in cancer progression and resistance, providing a foundation for future research and clinical applications.